A method for preparing battery-grade lithium carbonate based on recycled waste lithium batteries

By selectively leaching the positive electrode active substance by using proton hydrogen ionic liquid eutectic solvent and hydrogen peroxide in the recycling of waste lithium iron phosphate batteries, the defects of low separation and purification efficiency and high-temperature roasting in the prior art are solved, and the preparation and recycling process of high-purity lithium carbonate is simplified.

CN119018915BActive Publication Date: 2025-04-08ZHUHAI KELIXIN METAL MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411264498.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-04-08
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

When the prior art recovers lithium from waste lithium iron phosphate batteries, it is difficult to effectively and with high quality separation and purification of lithium, resulting in low purity and many impurities produced in lithium carbonate, which fails to meet the battery-grade standards. At the same time, the high-temperature roasting pretreatment process consumes a lot of energy and toxic gases pollute the environment.

Method used

Imethylene liquid of proton hydrogen was synthesized by one-step method as hydrogen bond acceptors, combined with polyethylene glycol and glycerol as hydrogen bond donors, and eutectic solvents were prepared for ionic liquid eutectic solvents, and hydrogen peroxide was used as oxidant. After discharge, disassembly, and aluminum removal of sodium hydroxide solution, lithium was selectively leaching of the positive electrode active substances, and finally, sodium carbonate solution was added to precipitate.

Benefits of technology

Without the need to remove the binder polyvinylidene fluoride, the prepared lithium carbonate meets the battery-grade standards, improves the leaching efficiency of lithium, shortens the recycling process, and is easy to produce in industrial use.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a method for preparing battery-grade lithium carbonate based on recycled waste lithium batteries, and belongs to the technical field of lithium battery recycling. The present invention uses imidazole and nitric acid to synthesize an ionic liquid containing proton hydrogen as a hydrogen bond acceptor through a one-step method, and uses polyethylene glycol and glycerol as hydrogen bond donors, so that the three of them prepare an ionic liquid low eutectic solvent through the action of hydrogen bonds, and then uses hydrogen peroxide as an oxidant to couple the ionic liquid low eutectic solvent to selectively leach lithium from the aluminum-free positive active material obtained after the waste lithium iron phosphate battery is discharged, disassembled, and aluminum-free with a sodium hydroxide solution, and finally ultrafiltration is performed to obtain a lithium-rich filtrate, which is then added with a sodium carbonate solution for precipitation to prepare lithium carbonate; compared with the prior art, the preparation method provided by the present invention can not only avoid the additional operation of removing the binder polyvinylidene fluoride, but also the prepared lithium carbonate meets the battery-grade standard.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery recycling, and in particular relates to a method for preparing battery-grade lithium carbonate based on recycled waste lithium batteries. Background Art

[0002] As a type of lithium battery, lithium iron phosphate battery is widely used in electronics, automobiles, energy and other fields due to its many characteristics such as high cycle stability and high specific energy. However, since lithium iron phosphate batteries will inevitably face the problem of scrapping during actual use, how to recover lithium from waste lithium iron phosphate batteries and prepare lithium carbonate has become a topic that people have been talking about for a long time. At present, most of the methods for recovering lithium from waste lithium iron phosphate batteries still use hydrometallurgical technology. Although hydrometallurgical technology has low recovery cost, is easy to industrialize, and can leach most of the lithium into the solution, it is difficult to effectively and efficiently separate and purify lithium in the subsequent process. The final prepared lithium carbonate is often of low purity and high impurities, and does not meet the battery grade standard. At the same time, before the actual recovery of lithium, it is necessary to undergo a pretreatment process of high-temperature roasting to achieve the purpose of removing the binder (PVDF, polyvinylidene fluoride) in the positive electrode material to avoid the adverse effect of the presence of the binder on the leaching efficiency. In the long run, this pretreatment process not only consumes a lot of energy, but also the toxic gases generated by high-temperature roasting will pollute the environment. Summary of the invention

[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing battery-grade lithium carbonate based on recycled waste lithium batteries. The present invention uses imidazole and nitric acid to synthesize an ionic liquid containing proton hydrogen as a hydrogen bond acceptor through a one-step method, and uses polyethylene glycol and glycerol as hydrogen bond donors, so that the three of them prepare an ionic liquid low eutectic solvent through the action of hydrogen bonds, and then uses hydrogen peroxide as an oxidant to couple the ionic liquid low eutectic solvent to selectively leach lithium from the aluminum-depleted positive active material obtained after the waste lithium iron phosphate battery is discharged, disassembled, and aluminum-depleted with a sodium hydroxide solution, and finally ultrafiltration is performed to obtain a lithium-rich filtrate, which is added with a sodium carbonate solution for precipitation to prepare lithium carbonate. Compared with the prior art, the preparation method provided by the present invention can not only avoid the additional operation of removing the binder polyvinylidene fluoride, but also the prepared lithium carbonate meets the battery-grade standard.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for preparing battery-grade lithium carbonate based on recycled waste lithium batteries, the method comprising the following steps:

[0006] (1) Discharge and disassemble the waste lithium iron phosphate battery to obtain the positive electrode material;

[0007] (2) adding 5-7 parts by weight of a positive electrode material to 30-35 parts by weight of a sodium hydroxide solution, stirring and mixing at room temperature for 4-6 hours, filtering, taking the filter residue, washing it with deionized water, and finally vacuum drying it at 50-60° C. until constant weight, thereby obtaining a positive electrode active material without aluminum;

[0008] (3) adding 80-100 parts by weight of an ionic liquid deep eutectic solvent and 6-7 parts by weight of hydrogen peroxide to the aluminum-removing positive electrode active material, stirring and leaching at 40-50° C. for 30-45 minutes, and ultrafiltration using an ultrafiltration membrane to obtain a filtrate;

[0009] (4) Add 25-30 parts by weight of sodium carbonate solution to the filtrate, stir and mix at 90-95° C. for 1-2 h, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60-80° C. until constant weight, and the preparation is completed.

[0010] As a preferred technical solution of the present invention, the discharge in step (1) refers to completely immersing the waste lithium iron phosphate battery in a sodium chloride solution with a mass fraction of 10% for 48 hours.

[0011] As a preferred technical solution of the present invention, the binder used in the positive electrode material in step (1) is polyvinylidene fluoride.

[0012] As a preferred technical solution of the present invention, the concentration of the sodium hydroxide solution in step (2) is 0.8-1 mol / L.

[0013] As a preferred technical solution of the present invention, the ionic liquid deep eutectic solvent in step (3) is prepared by the following steps:

[0014] Step A: adding 5-7 parts by weight of imidazole to 100 parts by weight of acetone, and then dropping 7-8 parts by weight of nitric acid solution under stirring in an ice bath, continuing to stir for 22-24 hours after the dropwise addition is completed, distilling, washing with ethyl acetate, and finally vacuum drying at 70-80° C. for 4-6 hours to obtain an ionic liquid hydrogen bond receptor;

[0015] Step B: Stir and mix the ionic liquid hydrogen bond acceptor, polyethylene glycol 400 and glycerol at 60-80° C. for 6-8 hours, and cool naturally to room temperature to complete the preparation.

[0016] Furthermore, the dripping rate in step A is controlled at 1-3 drops / s.

[0017] Furthermore, the mass fraction of the nitric acid solution in step A is 60-65%.

[0018] Furthermore, the distillation in step A refers to distillation at 70° C. under a pressure of -90 kPa until constant weight is achieved to remove volatiles.

[0019] Furthermore, in step B, the mass ratio of the ionic liquid hydrogen bond acceptor, the polyethylene glycol 400 and the glycerol is 13:18-20:14-15.

[0020] As a preferred technical solution of the present invention, the ultrafiltration using an ultrafiltration membrane in step (3) refers to ultrafiltration using an ultrafiltration membrane with a pore size of 30 nm, and the operating pressure is 0.2-0.4 MPa.

[0021] As a preferred technical solution of the present invention, the sodium carbonate solution in step (4) refers to a saturated sodium carbonate aqueous solution at room temperature.

[0022] As a preferred technical solution of the present invention, the washing with deionized water in step (4) refers to washing with deionized water at a temperature of 100°C.

[0023] Beneficial effects of the present invention:

[0024] (1) The present invention uses imidazole and nitric acid to synthesize an ionic liquid containing proton hydrogen as a hydrogen bond acceptor through a one-step process, and uses polyethylene glycol and glycerol as hydrogen bond donors, so that the three of them can prepare an ionic liquid low eutectic solvent through the action of hydrogen bonds, and then uses hydrogen peroxide as an oxidant to couple the ionic liquid low eutectic solvent to selectively leach lithium from the aluminum-free positive electrode active material obtained by discharging, disassembling, and removing aluminum with a sodium hydroxide solution of the waste lithium iron phosphate battery in sequence, and finally obtains a lithium-rich filtrate by ultrafiltration, and adds a sodium carbonate solution to precipitate and prepare lithium carbonate; compared with the prior art, the preparation method provided by the present invention can not only avoid the additional operation of removing the binder polyvinylidene fluoride, but also the prepared lithium carbonate meets the battery grade standard.

[0025] (2) The present invention creatively synthesizes a proton-type ionic liquid from imidazole and nitric acid to use it as a hydrogen bond acceptor, and then uses polyethylene glycol and glycerol as hydrogen bond donors to prepare an ionic liquid low eutectic solvent, which is coupled with hydrogen peroxide to selectively leach lithium from the dealuminized positive electrode active material obtained after the waste lithium iron phosphate battery is discharged, disassembled, and dealuminized with a sodium hydroxide solution. In the entire leaching system (leaching solution), hydrogen peroxide mainly plays a strong oxidizing role, gradually oxidizing the divalent iron of the lithium iron phosphate to trivalent iron, thereby forming an iron phosphate precipitate, thereby achieving selective leaching of lithium. On the one hand, the ionic liquid low eutectic solvent has a hydrogen bond donor. The ionic liquid eutectic solvent is polyethylene glycol and glycerol, which have very large polarity. After combining with the hydrogen bond receptor through the action of hydrogen bonds, according to the principle of like dissolves like, the three can synergistically produce a certain dissolution effect on the binder polyvinylidene fluoride (currently polyvinylidene fluoride is mostly dissolved by strong polar solvents), thereby realizing the stripping and removal of the binder on the surface of lithium iron phosphate, increasing the contact area with the leaching solution, and promoting the leaching of lithium. Finally, there is no need to perform additional binder removal operations before leaching, and efficient leaching can be achieved. On the other hand, due to the presence of proton hydrogen in the ionic liquid low eutectic solvent, the oxidation potential of hydrogen peroxide can be well improved, and the oxidation effect can be better achieved.

[0026] (3) The present invention does not require additional binder removal operations before leaching, and can directly add the leaching solution for leaching. Not only is the leaching efficiency not significantly affected, the obtained lithium carbonate meets the battery grade standard, but also the entire recovery process is shortened, which is easy to realize industrial production and has a very good application prospect. DETAILED DESCRIPTION

[0027] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0028] The waste lithium iron phosphate batteries in all the embodiments and comparative examples of the present invention are from Kolixin (Zhuhai) New Energy Co., Ltd.

[0029] Example 1

[0030] A method for preparing battery-grade lithium carbonate based on recycled waste lithium batteries, the method comprising the following steps:

[0031] (1) Discharge and disassemble the waste lithium iron phosphate battery to obtain the positive electrode material;

[0032] (2) adding 5 parts by weight of the positive electrode material to 30 parts by weight of the sodium hydroxide solution, stirring and mixing at room temperature for 4 hours, filtering, taking the filter residue, washing it with deionized water, and finally vacuum drying it at 50° C. until constant weight, to obtain the aluminum-free positive electrode active material;

[0033] (3) adding 80 parts by weight of an ionic liquid deep eutectic solvent and 6 parts by weight of hydrogen peroxide to the aluminum-removing positive electrode active material, stirring and leaching at 40° C. for 30 minutes, and ultrafiltration using an ultrafiltration membrane to obtain a filtrate;

[0034] (4) Add 25 parts by weight of sodium carbonate solution to the filtrate, stir and mix at 90° C. for 1 h, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60° C. until constant weight, and the preparation is completed.

[0035] The discharge in step (1) refers to completely immersing the waste lithium iron phosphate battery in a sodium chloride solution with a mass fraction of 10% for 48 hours.

[0036] The binder used for the positive electrode material in step (1) is polyvinylidene fluoride.

[0037] The concentration of the sodium hydroxide solution in step (2) is 0.8 mol / L.

[0038] The ionic liquid deep eutectic solvent of step (3) is prepared by the following steps:

[0039] Step A: add 5 parts by weight of imidazole to 100 parts by weight of acetone, then dropwise add 7 parts by weight of nitric acid solution under stirring in an ice bath, continue stirring for 22 hours after the dropwise addition is completed, distill, wash with ethyl acetate, and finally vacuum dry at 70° C. for 4 hours to obtain an ionic liquid hydrogen bond receptor;

[0040] Step B: The ionic liquid hydrogen bond acceptor, polyethylene glycol 400 and propylene glycol are stirred and mixed at 60° C. for 6 hours, and then naturally cooled to room temperature. The preparation is completed.

[0041] The rate of dripping in step A is controlled at 1 drop / s.

[0042] The mass fraction of the nitric acid solution in step A is 60%.

[0043] The distillation in step A refers to distillation at 70° C. under a pressure of −90 kPa until constant weight is achieved to remove volatiles.

[0044] In step B, the mass ratio of the ionic liquid hydrogen bond acceptor, the polyethylene glycol 400 and the glycerol is 13:18:14.

[0045] The ultrafiltration using an ultrafiltration membrane in step (3) refers to ultrafiltration using an ultrafiltration membrane with a pore size of 30 nm and an operating pressure of 0.2 MPa.

[0046] The sodium carbonate solution in step (4) refers to a saturated sodium carbonate aqueous solution at room temperature.

[0047] The washing with deionized water in step (4) refers to washing with deionized water at a temperature of 100°C.

[0048] Example 2

[0049] A method for preparing battery-grade lithium carbonate based on recycled waste lithium batteries, the method comprising the following steps:

[0050] (1) Discharge and disassemble the waste lithium iron phosphate battery to obtain the positive electrode material;

[0051] (2) adding 7 parts by weight of the positive electrode material to 35 parts by weight of the sodium hydroxide solution, stirring and mixing at room temperature for 6 hours, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 60° C. until constant weight, to obtain the aluminum-free positive electrode active material;

[0052] (3) adding 100 parts by weight of an ionic liquid deep eutectic solvent and 7 parts by weight of hydrogen peroxide to the aluminum-removing positive electrode active material, stirring and leaching at 50° C. for 45 minutes, and ultrafiltration using an ultrafiltration membrane to obtain a filtrate;

[0053] (4) Add 30 parts by weight of sodium carbonate solution to the filtrate, stir and mix at 95° C. for 2 h, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 80° C. until constant weight, and the preparation is completed.

[0054] The discharge in step (1) refers to completely immersing the waste lithium iron phosphate battery in a sodium chloride solution with a mass fraction of 10% for 48 hours.

[0055] The binder used for the positive electrode material in step (1) is polyvinylidene fluoride.

[0056] The concentration of the sodium hydroxide solution in step (2) is 1 mol / L.

[0057] The ionic liquid deep eutectic solvent of step (3) is prepared by the following steps:

[0058] Step A: adding 7 parts by weight of imidazole to 100 parts by weight of acetone, and then dropping 8 parts by weight of nitric acid solution under stirring in an ice bath, stirring for 24 hours after the dropping is completed, distilling, washing with ethyl acetate, and finally vacuum drying at 80° C. for 6 hours to obtain an ionic liquid hydrogen bond receptor;

[0059] Step B: The ionic liquid hydrogen bond acceptor, polyethylene glycol 400 and propylene glycol are stirred and mixed at 80° C. for 8 h, and then naturally cooled to room temperature to complete the preparation.

[0060] The rate of the dripping in step A is controlled at 3 drops / s.

[0061] The mass fraction of the nitric acid solution in step A is 65%.

[0062] The distillation in step A refers to distillation at 70° C. under a pressure of −90 kPa until constant weight is achieved to remove volatiles.

[0063] In step B, the mass ratio of the ionic liquid hydrogen bond acceptor, the polyethylene glycol 400 and the glycerol is 13:20:15.

[0064] The ultrafiltration using an ultrafiltration membrane in step (3) refers to ultrafiltration using an ultrafiltration membrane with a pore size of 30 nm and an operating pressure of 0.4 MPa.

[0065] The sodium carbonate solution in step (4) refers to a saturated sodium carbonate aqueous solution at room temperature.

[0066] The washing with deionized water in step (4) refers to washing with deionized water at a temperature of 100°C.

[0067] Example 3

[0068] A method for preparing battery-grade lithium carbonate based on recycled waste lithium batteries, the method comprising the following steps:

[0069] (1) Discharge and disassemble the waste lithium iron phosphate battery to obtain the positive electrode material;

[0070] (2) adding 6 parts by weight of the positive electrode material to 33 parts by weight of the sodium hydroxide solution, stirring and mixing at room temperature for 5 hours, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 55° C. until constant weight, to obtain the aluminum-free positive electrode active material;

[0071] (3) adding 90 parts by weight of an ionic liquid deep eutectic solvent and 6.5 parts by weight of hydrogen peroxide to the aluminum-removing positive electrode active material, stirring the mixture for 40 minutes at 45° C., and ultrafiltration using an ultrafiltration membrane to obtain a filtrate;

[0072] (4) Add 28 parts by weight of sodium carbonate solution to the filtrate, stir and mix at 93° C. for 1.5 h, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 70° C. until constant weight, and the preparation is completed.

[0073] The discharge in step (1) refers to completely immersing the waste lithium iron phosphate battery in a sodium chloride solution with a mass fraction of 10% for 48 hours.

[0074] The binder used for the positive electrode material in step (1) is polyvinylidene fluoride.

[0075] The concentration of the sodium hydroxide solution in step (2) is 0.9 mol / L.

[0076] The ionic liquid deep eutectic solvent of step (3) is prepared by the following steps:

[0077] Step A: add 6 parts by weight of imidazole to 100 parts by weight of acetone, then dropwise add 7.5 parts by weight of nitric acid solution under stirring in an ice bath, continue stirring for 23 hours after the dropwise addition is completed, distill, wash with ethyl acetate, and finally vacuum dry at 75° C. for 5 hours to obtain an ionic liquid hydrogen bond receptor;

[0078] Step B: The ionic liquid hydrogen bond acceptor, polyethylene glycol 400 and propylene glycol are stirred and mixed at 70° C. for 7 h, and then naturally cooled to room temperature to complete the preparation.

[0079] The dripping rate in step A is controlled at 2 drops / s.

[0080] The mass fraction of the nitric acid solution in step A is 63%.

[0081] The distillation in step A refers to distillation at 70° C. under a pressure of −90 kPa until constant weight is achieved to remove volatiles.

[0082] In step B, the mass ratio of the ionic liquid hydrogen bond acceptor, the polyethylene glycol 400 and the glycerol is 13:19:14.5.

[0083] The ultrafiltration using an ultrafiltration membrane in step (3) refers to ultrafiltration using an ultrafiltration membrane with a pore size of 30 nm and an operating pressure of 0.3 MPa.

[0084] The sodium carbonate solution in step (4) refers to a saturated sodium carbonate aqueous solution at room temperature.

[0085] The washing with deionized water in step (4) refers to washing with deionized water at a temperature of 100°C.

[0086] Comparative Example 1

[0087] On the basis of Example 1, step (2) is changed to adding 5 parts by weight of positive electrode material to 30 parts by weight of sodium hydroxide solution, then stirring and mixing at room temperature for 4 hours, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 50°C until constant weight to obtain a dealuminized positive electrode active material, and heat treating the dealuminized positive electrode active material at 500°C for 1.5 hours in a nitrogen atmosphere to obtain a dealuminized and binder-free positive electrode active material; in step (3), the dealuminized positive electrode active material is changed to the dealuminized and binder-free positive electrode active material; the rest remains unchanged.

[0088] Comparative Example 2

[0089] On the basis of Example 1, the ionic liquid eutectic solvent in step (3) is changed to an equal weight of sodium pyrosulfate aqueous solution; the mass fraction of the sodium pyrosulfate aqueous solution is 8%; and the rest remains unchanged.

[0090] Comparative Example 3

[0091] On the basis of Example 1, step (2) is changed to adding 5 parts by weight of positive electrode material to 30 parts by weight of sodium hydroxide solution, then stirring and mixing at room temperature for 4 hours, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 50°C until constant weight to obtain a dealuminized positive electrode active material, and heat treating the dealuminized positive electrode active material at 500°C for 1.5 hours under a nitrogen atmosphere to obtain a dealuminized and binder-free positive electrode active material; in step (3), the dealuminized positive electrode active material is changed to the dealuminized and binder-free positive electrode active material; in step (3), the ionic liquid low eutectic solvent is changed to an equal weight of sodium pyrosulfate aqueous solution; the mass fraction of the sodium pyrosulfate aqueous solution is 8%; and the rest remain unchanged.

[0092] Test Example 1

[0093] Lithium leaching rate and lithium carbonate purity test:

[0094] The lithium content of the positive electrode active material without aluminum and the filter residue separated after ultrafiltration in Examples 1-3 and Comparative Examples 1-3 is analyzed and tested by ICP-OES, and the lithium leaching rate can be calculated; at the same time, the purity of the lithium carbonate prepared in Examples 1-3 and Comparative Examples 1-3 is also tested, wherein the purity is compared with the standard content of the relevant chemical components in the standard YS / T582-2013 (i.e., the lithium carbonate content and the impurity content) to determine whether it meets the standard content.

[0095] Table 1. Lithium leaching rate and lithium carbonate purity test results

[0096] Lithium leaching rate / % Lithium carbonate content Impurity content Example 1 99.74 conform to conform to Example 2 99.80 conform to conform to Example 3 99.68 conform to conform to Comparative Example 1 99.77 conform to conform to Comparative Example 2 95.49 Not Compliant Too much iron Comparative Example 3 99.01 conform to Too much iron

[0097] Comparison between Example 1 and Comparative Examples 1-3 shows that:

[0098] The difference between Comparative Example 1 and Example 1 is that a heat treatment process is performed in advance to remove the binder.

[0099] The difference between Comparative Example 2 and Example 1 is that the ionic liquid deep eutectic solvent in the leaching system is changed to a sodium pyrosulfate aqueous solution.

[0100] The difference between Comparative Example 3 and Example 1 is that a heat treatment process is performed in advance to remove the binder, and at the same time, the ionic liquid low eutectic solvent in the leaching system is also changed to a sodium pyrosulfate aqueous solution.

[0101] From Test Example 1, it can be seen from the comparison between Example 1 and Comparative Examples 1-3 that the lithium carbonate prepared by the present invention has high purity and reaches the battery-grade standard, and the lithium leaching rate is high when recycling lithium from waste lithium iron phosphate batteries; although Comparative Example 1 has undergone a heat treatment process in advance to remove the binder, its lithium leaching rate is not significantly improved; Comparative Example 2 replaces the ionic liquid low eutectic solvent with the sodium pyrosulfate aqueous solution of the prior art, not only the lithium leaching rate has been greatly reduced, but the prepared lithium carbonate is also difficult to reach the battery-grade standard; Compared with Comparative Example 2, Comparative Example 3 has an additional step of a prior heat treatment process to remove the binder. Although the lithium leaching rate has been improved to a certain extent, it is still not as good as Example 1. At the same time, the impurity content of the lithium carbonate prepared by it does not meet the battery-grade standard.

[0102] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing battery-grade lithium carbonate based on recycled waste lithium batteries, characterized in that: The method comprises the following steps: (1) Discharge and disassemble the waste lithium iron phosphate battery to obtain the positive electrode material; (2) adding 5-7 parts by weight of a positive electrode material to 30-35 parts by weight of a sodium hydroxide solution, stirring and mixing at room temperature for 4-6 hours, filtering, taking the filter residue, washing it with deionized water, and finally vacuum drying it at 50-60° C. until constant weight, thereby obtaining a positive electrode active material without aluminum; (3) adding 80-100 parts by weight of an ionic liquid deep eutectic solvent and 6-7 parts by weight of hydrogen peroxide to the aluminum-removing positive electrode active material, stirring and leaching at 40-50° C. for 30-45 minutes, and ultrafiltration using an ultrafiltration membrane to obtain a filtrate; (4) adding 25-30 parts by weight of sodium carbonate solution to the filtrate, stirring at 90-95° C. for 1-2 h, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 60-80° C. until constant weight, and the preparation is completed; The binder used in the positive electrode material of step (1) is polyvinylidene fluoride; The ionic liquid deep eutectic solvent in step (3) is prepared by the following steps: Step A: adding 5-7 parts by weight of imidazole to 100 parts by weight of acetone, and then dropping 7-8 parts by weight of nitric acid solution under stirring in an ice bath, continuing to stir for 22-24 hours after the dropwise addition is completed, distilling, washing with ethyl acetate, and finally vacuum drying at 70-80° C. for 4-6 hours to obtain an ionic liquid hydrogen bond receptor; Step B: Stir and mix the ionic liquid hydrogen bond acceptor, polyethylene glycol 400 and glycerol at 60-80° C. for 6-8 hours, and cool naturally to room temperature to complete the preparation.

2. A method for preparing battery-grade lithium carbonate based on recycled waste lithium batteries according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in step (2) is 0.8-1 mol / L.

3. A method for preparing battery-grade lithium carbonate based on recycled waste lithium batteries according to claim 1, characterized in that: The dripping rate in step A is controlled at 1-3 drops / s.

4. A method for preparing battery-grade lithium carbonate based on recycled waste lithium batteries according to claim 1, characterized in that: The mass fraction of the nitric acid solution in step A is 60-65%.

5. A method for preparing battery-grade lithium carbonate based on recycled waste lithium batteries according to claim 1, characterized in that: The distillation in step A refers to distillation at 70° C. under a pressure of −90 kPa until constant weight is achieved to remove volatiles.

6. A method for preparing battery-grade lithium carbonate based on recycled waste lithium batteries according to claim 1, characterized in that: In step B, the mass ratio of the ionic liquid hydrogen bond acceptor, the polyethylene glycol 400 and the glycerol is 13:18-20:14-15.

7. A method for preparing battery-grade lithium carbonate based on recycled waste lithium batteries according to claim 1, characterized in that: The ultrafiltration using an ultrafiltration membrane in step (3) refers to ultrafiltration using an ultrafiltration membrane with a pore size of 30 nm and an operating pressure of 0.2-0.4 MPa.

8. A method for preparing battery-grade lithium carbonate based on recycled waste lithium batteries according to claim 1, characterized in that: The sodium carbonate solution in step (4) refers to a saturated sodium carbonate aqueous solution at room temperature.

Citation Information

Patent Citations

  • Method for effectively recycling positive electrode material of waste lithium iron phosphate battery

    CN116553502A

  • Method for recovering lithium in waste lithium iron phosphate battery by using novel eutectic solvent

    CN116732343A

  • Low transition temperature mixtures or deep eutectic solvents and processes for preparation thereof

    US20160122676A1